RANCANG BANGUN SISTEM INFORMASI PERSEDIAAN BARANG HOTEL BERBASIS WEB PADA HOTEL PATRA COMFORT JAKARTA - Gelar Bayu Adirama; Muhammad Feizal (CV. Multi Kreasi Media, 2022)
Hotel Patra Comfort Jakarta is a company engaged in the hospitality sector. Hotel Patra Comfort Jakarta has problems, namely monthly inventory still uses Microsoft Word and Microsoft Excel as documentation and employees do not know inventory information, which is only centered on one particular computer device in knowing inventory information in the hotel. This study aims to build a website-based hotel inventory information system at the Patra Comfort Hotel, Jakarta. The research method used is the method of collecting observation data, and interviews. The system development method used is Waterfall and the system design uses UML (Unified Modeling Language). Database analysis and design tools use Entity Relationship Diagram (ERD) and are transformed into Logical Record Structure (LRS), programming language using PHP and database using MySQL. The test method uses Blackbox testing. The result of this research is to produce a website-based hotel inventory information system in order to help Patra Comfort Hotel Jakarta in managing the data of goods in the hotel.